An Improved Spread Spectrum Technique for Robust Watermarking - Malvar, Henrique; Florencio, Dinei; Malvar, Henrique S. (IEEE, 2002)
This paper introduces a new watermarking modulation technique, which we call improved spread spectrum (ISS). Unlike in traditional spread spectrum (SS), in ISS the carrier signal does not act as a noise source, leading significant performance gains. In typical examples, the gain of ISS over SS is 20 dB or more in signal-to-noise ratio or 20 orders of magnitude or more in error probability. The proposed method achieves roughly the same noise robustness gain as quantization index modulation (QIM). Nevertheless, while QIM is quite sensitive to amplitude variations, ISS is as robust in practice as traditional SS.